GAYA KOMUNIKASI DAN PERUBAHAN RELASI DALAM PERKAWINAN IMPAL SUKU KARO DI KABUPATEN DELI SERDANG - Barus, Nia Nuryanti (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
Impal marriage is a traditional custom of the Karo ethnic group in North Sumatra, in which a man marries his maternal cousin. Although it is culturally believed to strengthen family ties, in practice, the relationship between mother-in-law and daughter-in-law in impal marriages often leads to conflict. This study aims to analyze the forms of conflict and the communication styles that develop between mother-in-law and daughter-in-law in this context, focusing on the Karo community in Deli Serdang Regency. Using a qualitative approach and case study method, data were collected through in-depth interviews and observation of six mother-in-law and daughter-in-law pairs, along with one key triangulation informant from the local customary leadership. The findings reveal that conflict is triggered by expectancy violations, value differences, shifting social roles, and ineffective communication styles. Expectancy Violation Theory and Face Negotiation Theory are employed to explain the dynamics of these conflicts. The transition in relationship status from aunt and niece to mother-in-law and daughter-in-law creates identity tension and cultural expectations that, if not addressed through open communication, may lead to the breakdown of interpersonal relationships within traditional family structures.